Comparative analysis of behavioral and transcriptional variation underlying CO2 sensory neuron function and development in Drosophila. Issue 4 (2nd October 2017) - Pan, Jia Wern; McLaughlin, Joi; Yang, Haining; Leo, Charles; Rambarat, Paula; Okuwa, Sumie; Monroy-Eklund, Anaïs; Clark, Sabrina; Jones, Corbin D.; Volkan, Pelin Cayirlioglu
ABSTRACT: Carbon dioxide is an important environmental cue for many insects, regulating many behaviors including some that have direct human impacts. To further improve our understanding of how this system varies among closely related insect species, we examined both the behavioral response to CO2 as well as the transcriptional profile of key developmental regulators of CO2 sensory neurons in the olfactory system across the Drosophila genus. We found that CO2 generally evokes repulsive behavior across most of the Drosophilids we examined, but this behavior has been lost or reduced in several lineages. Comparisons of transcriptional profiles from the developing and adult antennae for subset these species suggest that behavioral differences in some species may be due to differences in the expression of the CO2 co-receptor Gr63a . Furthermore, these differences in Gr63a expression are correlated with changes in the expression of a few genes known to be involved in the development of the CO2 circuit, namely dac, an important regulator of sensilla fate for sensilla that house CO2 ORNs, and mip120, a member of the MMB/dREAM epigenetic regulatory complex that regulates CO2 receptor expression. In contrast, most of the other known structural, molecular, and developmental components of the peripheral Drosophila CO2 olfactory system seem to be well-conserved across all examined lineages. These findings suggest that certain components of CO2 sensory ORN development may be more evolutionarily labile, and may contribute to differences in CO2 -evoked behavioral responses across species.